Planeación, atención y flexibilidad mental como indicadores de funcionamiento ejecutivo en universitarios que practican deporte y que no practican deporte (2016)
The following project aims to characterize the executive functioning in terms of attention, planning and mental flexibility in sportive and non-sportive students of a private university in Cartagena. A quantitative cutoff methodology was used with a nonexperimental design, in which, the measuring instruments used were the train making test and the labyrinths of porteus with the participation of students of both genders between the ages of eighteen and twenty-eight. Regarding the results obtained, it was found that the population of sportive and non-sportive have adequate levels of sustained attention and sequencing that was evidenced in the performance obtained from the trail making test. On the other hand, the results obtained in the labyrinth test of porteus reveal deficient levels in confrontation, which is understood as difficulties to persevere in tasks that involve planning and attention at the same time.